Policy competition for foreign direct investment in the Caribbean Basin : Costa Rica, the Dominican Republic and Jamaica - Mortimore, Michael (UN SantiagoCL, 1998)
Considers three main categories of policy competition for foreign investment: (a) competition through the provision of direct and indirect subsidies, tax holidays and other similar financial incentives, (b) competition through the strengthening of a market economy with an adequate legal system, labour and environmental standards, intellectual property rights and regional integration agreements and (c) competition through the development of production factors and infrastructure needed for an efficient economic performance.